Burnout among University Educators: Mapping Research Trends and Identifying Risk Factors through Systematic Literature Review - Wahyudi Dwi Hartanto (FKIP - Universitas Riau, 2026)
Burnout among university educators has become a critical issue due to its potential to affect the quality of education. The relevance of this topic has increased alongside rising job demands, the digitalization of education, and changes in the higher education work environment. This study aims to map research trends and identify factors influencing burnout among university educators through a systematic literature review (SLR) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. From an initial 118 articles identified in the Scopus database, 38 articles were selected based on the inclusion and exclusion criteria. The findings show an increasing publication trend in recent years, with noticeable fluctuations beginning in 2020 during the COVID-19 pandemic. Most studies originate from China, while contributions from other countries remain limited. The literature is largely dominated by the Job Demands–Resources and Conservation of Resources theory, with most studies employing quantitative survey-based approaches. Publications are primarily concentrated in reputable journals in psychology, education, and public health. The review also identifies various factors contributing to burnout, confirming its multidimensional nature. This study contributes to the theoretical understanding of burnout dynamics and offers practical implications for developing policies that support the well-being of university educators.